2021
DOI: 10.1002/cbic.202100016
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Anti‐biofilm Activity of the Human Breast Milk Glycoprotein Lactoferrin against Group B Streptococcus

Abstract: Group B Streptococcus (GBS) is an encapsulated Gram‐positive human pathogen that causes invasive infections in pregnant hosts and neonates, as well as immunocompromised individuals. Colonization of the human host requires the ability to adhere to mucosal surfaces and circumnavigate the nutritional challenges and antimicrobial defenses associated with the innate immune response. Biofilm formation is a critical process to facilitate GBS survival and establishment of a replicative niche in the vertebrate host. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 77 publications
1
38
0
Order By: Relevance
“…H . pylori cells have not been observed to synthesize siderophores, however they do produce a variety of siderophore receptors and iron acquisition functions, including lactoferrin and transferrin receptors which are highly expressed in iron‐deficient conditions, [28] which could aid in this process in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…H . pylori cells have not been observed to synthesize siderophores, however they do produce a variety of siderophore receptors and iron acquisition functions, including lactoferrin and transferrin receptors which are highly expressed in iron‐deficient conditions, [28] which could aid in this process in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…pylori virulence. Our group has also demonstrated that lactoferrin possesses antimicrobial properties against other bacterial pathogens such as Streptococcus agalactiae (Group B Streptococcus) [28] and Acinetobacter baumannii [36] through the conserved immune strategy of nutritional immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human lactoferrin was isolated from breast milk as previously described ( Lu et al., 2021 ). Briefly, expressed human breast milk was gathered from 17 healthy donors between 3 days and 3 months post-partum and stored between -80 and -20˚C.…”
Section: Methodsmentioning
confidence: 99%
“…Lactoferrin is a glycoprotein that contains two iron binding sites ( Weinberg, 1975 ) and was shown to have antimicrobial activity against a wide range of bacterial, viral, and fungal pathogens ( Lu et al., 2020 ). Indeed, our previous study demonstrated that human breast milk lactoferrin has antimicrobial and anti-biofilm activity against GBS and inhibits some GBS strains from adhering to human gestational membranes ( Lu et al., 2021 ). In this study, we advanced our findings by analyzing the antimicrobial and anti-biofilm effects of lactoferrin against a larger panel of clinical GBS strains that vary by capsular serotype, ST, isolation source, and clinical presentation.…”
Section: Introductionmentioning
confidence: 99%